Social transformation of indigenous communities in forming citizenship identity: Case study of the Tobelo Dalam tribe in Tukur-Tukur hamlet, Dodaga village, East Halmahera - Noe, Wahyudin; Bunta, Abd. Firman; Abbas, Irwan; Zahra, Aulia Fatimatuz; Triyanto; Yunus, Rasid; Madiong, Dwi Ayu Ratnasari A. (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
The Tobelo Dalam tribe actively represents an indigenous community in Indonesia, consistently maintaining biodiversity in various forest areas of Halmahera, North Maluku. The expansion of timber companies and the mining industry threatens the roaming area of the Tobelo Dalam tribe. Over time, some experienced a cultural shift from nomadic life, embracing modern values while maintaining their identity as an inland community that fully utilises forest products to meet their living needs. This study analyses the existence of the Tobelo Dalam tribe in the Tukur-Tukur hamlet, Dodaga village, East Halmahera and examines how their social transformation patterns shape a citizenship identity. This study employs a qualitative approach through a case study method. Collect data using observation, interviews, and documentation techniques. We analysed the collected data using data reduction, presentation, and verification techniques. The research findings show that the Tobelo Dalam tribe in the Tukur-Tukur hamlet, an indigenous community that values the forest ecosystem, has undergone a shift in modern lifestyle due to government policies promoting modern living standards for the community, and internal encouragement from the tribe to leave the forest zone for settlements. The social transformation pattern of the Tobelo Dalam tribe in the Tukur-Tukur hamlet reveals three domains: political factors, cultural factors, and social factors, which are evident in aspects of religion, education, social behaviour, and economy. This study's findings offer stakeholders valuable insights to protect the sustainability of forests and indigenous communities on Halmahera Island from mining impacts.